Muslim Families' Resilience Post-Eruption Mount Semeru: The Quest of Women’s Roles in Family - Shofi, Muhammad Aminuddin; bin Budin, Azmi (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2024)
Women play a crucial role in maintaining family resilience. Their role becomes even more tested in critical situations. This article examines the resilience of Muslim families after the Semeru eruption and highlights the vital role of women in rebuilding family strength in Sumbermujur village, Lumajang, East Java. This article uses a sociological approach, utilizing structural-functional theory. This article reveals that, sequentially, post-relocation, the survivors of the Semeru eruption were impacted economically, psychologically, culturally, and physically. Significantly, they lost assets and faced difficulties finding new jobs, which emerged as the dominant effect. This article shows that women are crucial to building family resilience. From the perspective of structural-functional theory, adaptation is evident in how women must adapt to new physical, psychological, socio-cultural, and economic conditions. This adaptation that aims to achieve family independence and well-being manifests their goals. How women share roles dynamically and flexibly in fulfilling each other's responsibilities reflects integration. The interaction of religious, legal, and social norms that always guide women in performing their roles shows latency. Thus, the role of women in preserving family resilience can be seen as an implementation of their religious responsibilities to achieve a harmonious family in critical situations.